(untitled) (The Review of Diabetic Studies, 2025)
Background: The hospital-at-home (HaH) model, providing acute inpatient-level care in a patient’s residence, has demonstrated efficacy in improving outcomes and patient satisfaction for specific conditions. While evidence is robust, widespread, equitable scaling remains a significant health system challenge. Health administrators play a pivotal role in navigating this complex implementation landscape. Aim: This narrative review synthesizes the evidence from 2010-2022 on the role of health administrators in scaling virtual hospital-at-home programs, focusing on the barriers they must overcome, the financing models they must develop, and the clinical and operational outcomes achieved. Methods: A systematic search was conducted across PubMed, CINAHL, Scopus, and Business Source Complete. Literature including peer-reviewed studies, reviews, policy analyses, and case reports was analyzed thematically to identify administrative strategies, structural challenges, and financial frameworks. Results: Key administrative barriers include restrictive regulatory and licensure frameworks, workforce reconfiguration needs, and technological infrastructure requirements. Successful scaling is underpinned by innovative financing models, including value-based payment bundles, CMS waiver programs, and risk-sharing partnerships. Administratively-led HaH programs report equivalent or superior clinical outcomes, high patient satisfaction, and significant reductions in cost and healthcare utilization. Conclusion: Health administrators are the critical architects of successful HaH scale. Their strategic focus must be on crafting sustainable financial models, advocating for supportive policy, and leading interdisciplinary operational integration to realize the model’s full potential for population health.